Permeability to water in a tight epithelium: Possible modulating action of gap junctions - Orce, Gabriel Guillermo F. (2004)
Osmotic water flow (Jw) across tight distal nephron epithelial membranes increases upon exposure to vasopressin: following binding of the hormone to its receptors, intracellular cyclic AMP concentration increases, leading to insertion of aquaporins in the apical membrane. The involvement of intercellular communication in the process, however, has not been adequately explored. Octanol, 1.2 × 10-3 M, a gap junction inhibitor, significantly reduced Jw (expressed as mg·20 min-1) in isolated toad urinary bladders (a model of the distal nephron) subjected to a transepithelial osmotic gradient and exposed to agents mimicking the vasopressin-triggered mechanism: oxytocin, 50 mIU·mL-1 (from 185.3 ± 28.0, P < 0.001, to 69.0 ± 23.6, P < 0.05; Pdiff < 0.01, n = 6), and cyclic AMP, 2.5 × 10-3 M (from 98.0 ± 32.6, P < 0.02, to 31.0 ± 13.9, NS; Pdiff < 0.05, n = 12), without altering the effect of nystatin, 450 U·mL-1, which increases Jw via a mechanism unrelated to apical aquaporin insertion (163.2 ± 16.3, P < 0.001, in controls vs. 150.3 ± 10.4, P < 0.001, in octanol-treated bladders; Pdiff: NS, n = 6). Another gap junction blocker, carbenoxolone, 2.0 × 10-4 M (CBX), exerted similar effects on the responses to oxytocin, 100 mIU·mL-1, reducing the response from 256.7 ± 33.6, P < 0.001, to 102.7 ± 10.4, P < 0.001; Pdiff < 0.01, n = 6) and nystatin, which was unaffected (95.0 ± 20.9, P < 0.01, vs. 132.0 ± 27.0, P < 0.01; Pdiff: NS, n = 6). Our results suggest that either gap junctions or, alternatively, unapposed gap junction hemichannels, may be important in the regulation of Jw in the isolated toad bladder, by modulating a step in the physiological process leading to increased apical membrane permeability.